Power at the expense of diffuse interests? The European Parliament as a legitimacy-seeking institution. Issue 1 (1st January 2020) - Greenwood, Justin; Roederer-Rynning, Christilla
ABSTRACT: Has the European Parliament (EP)'s acquisition of legislative powers diluted its traditional support for diffuse interests? This article considers the various arguments that challenge the EP's reputation as a champion of diffuse interests and advances an alternative interpretation grounded in the idea of the EP as a legitimacy seeking institution. These arguments are explored in light of EP strategies of public engagement. Whilst previous analyses have been centred on the EP itself, we broaden the empirical focus to examine patterns of diffuse interest engagement with the EP. We find variance in the way diffuse advocates engage with the EP, and identify a driver of differentiation among NGO advocates of diffuse interests organized at EU level. We draw on interviews with NGOs, representatives from EU political institutions, as well as data from the Transparency Register to assess NGO/EP interactions.